Exploring patient-centred care and help-seeking behaviour among infertile females in Jeddah governorate, Saudi Arabia: a mixed method approach - Webair, Hana Hasan Mohammed (2023)
This thesis aims to explore the concept of PCIC, to develop and validate an instrument to measure it, and to determine the relationship of PCIC with the helpseeking behaviour (HSB) among Arab infertile women. It was conducted in Jeddah Governorate, Saudi Arabia in three phases from January 2017 to December 2022 using mixed-method approach. Phase I was a qualitative study that explored the concept of PCIC among infertile women who received medical care within the last six months. Women were recruited purposefully until saturation was reached. Fourteen in-depth interviews were conducted and analysed by inductive-deductive thematic analysis. Phase II was a validation study to develop and validate a Patient-Centred Infertility Questionnaire for Female clients (PCIQ-F). PCIC-F was formulated in the light of the results of the qualitative study and literature review. A pilot study was then carried out on an online convenience sample of 201 infertile women to define PCIQ-F latent constructs using exploratory factor analysis. Furthermore, a field study was undertaken on 316 infertile women to test PCIQ-F psychometric properties and to produce the final version. Phase III was a cross-sectional online survey which examined the relationship of HSB with the PCIC during the last six months by logistic regression and path analysis in structural equation modelling. The moderation effect of the type of infertility treatment on this relationship was tested by multi-group analysis. The tool was PCIQ-F with added questions about the concurrent use of non-medical treatment during infertility medical care. A total of 466 women were included. Phase I identified nine PCIC dimensions valued by Arab women; accessibility; minimising costs; staff attitude and communication; information and education; physical comfort; privacy; staff competence; psychological and emotional support; and continuity and coordination of care. PCIQ-F comprises four sections: introduction, background characteristics, PCIC, and overall quality assessment. PCIC section is divided into four domains (24 items): comprehensiveness of care, communication and information; patient education and support; patient empowerment; and physical comfort. Statistical analysis proved the validity and reliability of PCIQ-F. Phase III found no significant effect of PCIC on seeking non-medical care (p=0.078, AOR 0.86, 95%CI 0.73, 1.02). However, patient empowerment and physical comfort showed a significant effect, p=0.023, 0.032 AOR 1.20, 0.83 95%CI 1.02,1.41; 0.71,0.99, respectively. Furthermore, PCIC, patient empowerment, and physical comfort showed direct negative effect on the number of sources seen for infertility with p=0.001 for all, beta –1.29, -0.534,–0.257, S.E.0.128, 0.071,0.042, respectively. The type of infertility treatment partially moderated the relationship between PCIC and HSB. In conclusion, the concept of PCIC from Arab women’s perspectives embraces nine dimensions. Based on these dimensions, a valid and reliable tool (PCIQ-F) was developed. PCIC has a negative effect on seeking non-medical care, which is moderated by the treatment type. We recommend implementing PCIC in health facilities and measuring its implementation using PCIQ-F, which could improve women's HSB.